Successful Primary PCI in Left Anterior Descending Artery Managing Acute Myocardial Infarction - Safiuddin, Mohammad; Bari, Ahmed Saiful; Rashid, Md Sharifur; Hasan, Md Hasibul; Hasan, Md Nazmul; Islam, Lohani Md Tajul (University Heart Journal, 2015)
Coronary reperfusion with primary percutaneous coronary intervention (PPCI) or fibrinolytic therapy improves outcomes in patients with acute ST elevation myocardial infarction (STEMI) or an acute myocardial infarction (AMI) with a new or presumably new left bundle branch block or a true posterior MI. If performed in a timely fashion, PPCI is the reperfusion therapy of choice compared to fibrinolysis because it achieves a higher rate of TIMI 3 flow. Here we describe a case of acute ST elevated anterior myocardial infarction managed with primary percutaneous coronary intervention with the insertion of a drug eluting stent in the Left anterior descending Artery without any procedural complication. University Heart Journal Vol. 10, No. 1, January 2014; 45-46